The Significance of CXCL1 and CXCL8 as Well as Their Specific Receptors in Colorectal Cancer - Łukaszewicz-Zając, Marta (Cancer Manag Res, 2020)
Every year, almost 2 million people develop colorectal cancer (CRC), which makes it the fourth most common malignancy worldwide. It is also estimated that approximately 48% of CRC patients will die from the disease. Thus, noninvasive and accurate methods for early detection and prevention of CRC are sorely needed. It is suggested that C-X-C motif ligand 1 (CXCL1) and C-X-C motif ligand 8 (CXCL8) as well as their cognate receptors can mediate tumor growth, proliferation, survival, neoangiogenesis and metastasis of malignant cells, including CRC. However, little is known about the clinical significance of these proteins as potential biomarkers for CRC. Therefore, in our review, we performed a comprehensive literature search using the PubMed database to identify original articles that investigated whether CXCL1 and CXCL8 and their receptors play a role in CRC pathogenesis. In summary, our review highlighted the potential significance of CXCL1/CXCR2 and CXCL8/CXCR1,-2 in the diagnosis and progression of CRC as well as indicated their potential therapeutic significance. However, given the non-specific nature of analyzed chemokines and a small number of studies concerning the assessment of blood concentration of these proteins in CRC patients, investigations need to be continued in the future before selected chemokines could be established as biomarkers for CRC.